Citra Perempuan dalam Legenda Putri Cermin Cina - Dedi Febriyanto; Yessi Fitriani; Puspa Indah Utami (ESTETIK : Jurnal Bahasa Indonesia, 2023)
Feminist ideology, especially regarding the image of women in literary works, can open up society's views more broadly and comprehensively regarding various gender issues. The aim of this research is to describe the image of the main female character in the Jambi folk tale Legend of the Putri Cermin Cina. The research was conducted using a descriptive qualitative method. Research data in the form of sentence quotations was obtained through reading and note-taking techniques. Next, the data was analyzed using interactive techniques. The results of this research show that the main female character in the Legend of the Chinese Mirror Princess is depicted as a social woman who has high complexity. Judging from her physical image, the main female character is depicted as a beautiful woman, smiling, polite in speaking, and graceful. Judging from the psychological aspect, the main female character is depicted as someone who is soft-hearted and always happy. In her role in the family, the female character is described as careful, agile, diligent, skilled, and devoted to her parents. As for their role in community life, female characters are described as having a high social spirit, being very loved by the community, and having noble character.